Ligation-mediated amplification of RNA from murine erythroid cells reveals a novel class of beta globin mRNA with an extended 5'-untranslated region. - Volloch, V (1994)
Ligation-mediated RNA amplification was developed as a tool for analysis and determination of the termini of RNA molecules [Volloch et al. (1991) Proc. Natl. Acad. Sci. USA 88: 10671-10675]. In this approach, T4 RNA ligase is used to join cellular RNA with a defined ribo-oligonucleotide. Although several additional enzymatic steps are involved in this type of analysis, the reliability of the entire procedure is determined by the initial ligation step, which marks and preserves the termini of cellular RNA molecules. We applied this approach to the analysis of the 5' terminus of beta globin mRNA in various murine erythroid cells. As expected, we detected RNA molecules with 5' ends terminating at the regular cap site as well as globin RNA molecules truncated at the 5' end. Unexpectedly, we also detected a class of beta globin mRNA which is identical to regular beta globin mRNA in every respect but contains 17, 29, or 31 additional nucleotides 5' to the regular cap site. These extensions correspond precisely to the genomic segments just upstream of the regular cap site and are probably generated by initiation of transcription of the globin gene upstream from the regular cap site. It is likely that the extended globin RNA is transcribed not from the TATA promoter, which regulates the transcription of regular murine globin mRNA, but from the GATA regulatory element located 30 nucleotides upstream of the 31-nucleotide extension, in a position identical to that of the active GATA promoter of the TATA-less chicken beta globin gene. The evolutionary conservation of this relationship suggests the importance of the GATA promoter element of the mouse beta globin gene and its possible involvement in developmental regulation of expression of this gene.